Preparation and application of glucono-δ-lactone-induced gel of transglutaminase cross-linked black bean protein isolate-whey protein isolate: Effect of ultrasound pretreatment - Yuexin Liu; Yichen Zhang; Fengjuan Dong; Qingkui Zhao; Shuang Zhang; Chen Tan (Ultrasonics Sonochemistry)
A glucono-δ-lactone induced gel was prepared using transglutaminase cross-linked black bean protein-whey protein to deliver riboflavin. Ultrasound pretreatment was found to positively affected gels’ hardness, water holding capacity and elasticity. The hardness and elasticity of protein gel pretreated by ultrasound at 360 W were the best, and the water holding capacity of protein gel pretreated by ultrasound at 480 W was the best. These improvements could be attributed to the enhanced hydrophobic interactions and disulfide bonds between proteins by ultrasound pretreatment, which could facilitate a dense network structure, as observed by scanning electron microscope. The dense network of ultrasound-pretreated protein gel effectively protected the riboflavin, and the riboflavin release was reduced by 52 % during gastric digestion for the gel produced at ultrasound power of 360 W, enabling a large amount of riboflavin for absorption and utilization in the intestine. These findings will guide the design of double protein complex gels, providing possible avenues for use as carriers of biologically active substances such as riboflavin.